EXPLORING THE IMPLEMENTATION OF DUOLINGO MEDIA FOR ASSIGNMENT IN LEARNING ENGLISH - Fauzan Fauzan; Usman Kasim (English Education Journal, 2020)
This research is aimed at investigating the use of Duolingo media in learning English as students’ assignment at eleventh grade students of methodist senior high school. A case study was used as the research design. The participant was an English teacher and 30 eleventh-grade students of Methodist school. The data were collected by interviewing the teacher and giving students questionnaires in order to attain the data needed for this reseach. The interview result was analysed by using procedure of data analysis from Miles and Huberman (1994), while the result data of the questionnaire was analyzed by using percentage formula from Sudjana (2002). The research finding shows that the teacher and students consider that using the Duolingo media was effective in learning English because it improved students’ willingness to do the assignment at home via Duolingo media and language skills in learning English. In conclusion, Duolingo media can be applied in by students to finish English assignment at home because it maked students excited and interested to do the homework by Duolingo.